High-energy flexible supercapacitor-synergistic effects of polyhydroquinone and RuO2 center dot xH(2)O with microsized, few-layered, self-supportive exfoliated-graphite sheets - Muniraj, Vedi Kuyil Azhagan; Dwivedi, Pravin Kumari; Tamhane, Parikshit Shivaji; Szunerits, Sabine; Boukherroub, Rabah; Shelke, Manjusha Vilas (ACS Applied Materials & Interfaces, 2019)
An effective and straightforward route for tailoring the self-supporting, exfoliated flexible graphite substrate (E-FGS) using electrochemical anodization is proposed. E-FGS has essential features of highly exfoliated, few-layered, two-dimensional graphite sheets with the size of several tens of micrometers, interconnected along the axis of the substrate surface. The novel hierarchical porous structural morphology of E-FGS enables large active sites for efficient electrolyte ion and charge transport when used as electrode material for a supercapacitor. In order to effectively utilize this promising E-FGS electrode for energy storage purpose, a ternary composite is further synthesized with pseudocapacitive polyhydroquinone (PHQ) and hydrous RuO2 (hRO). hRO is synthesized via a sol-gel route, while electropolymerization is utilized for the electrodeposition of PHQ over E-FGS. Ultimately, the fabricated self-supporting E-FGS-based flexible supercapacitor is capable of delivering areal specific capacitance values as high as 378 mF cm(-2) at a current density of 1 mA cm(-2). Addition of the pseudocapacitive component to the E-FGS texture leads to similar to 10 times increase of the electrochemical charge storage capability. The imposition of mechanical forces to this flexible supercapacitor device results in trivial changes in electrochemical properties and is still capable of retaining 91% of the initial specific capacitance after 10 000 cycles. Alongside, the fabricated symmetrical solid-state flexible device exhibited a high energy density of 8.4 mu Wh cm(-2). The excellent performance along with the ease of synthesis and fabrication process of the flexible solid-state supercapacitor device using PHQ/hRO/E-FGS holds promise for large-scale production.
Keywords: graphite exfoliation; polyhydroquinone; ruthenium oxide; solid-state flexible supercapacitor; Ternary Composite

Flexible energy storage device based on poly(N-phenylglycine), an incentive-energy pseudocapacitive conducting polymer, and electrochemically exfoliated graphite sheets - Muniraj, Vedi Kuyil Azhagan; Boukherroub, Rabah; Shelke, Manjusha Vilas (ACS Sustainable Chemistry & Engineering, 2020)
Poly(N-phenylglycine) (PNPG), an original pseudocapacitive conjugative conducting polymer (CP), was synthesized by the electro-oxidative polymerization method. The synthesis process involves in situ polymerization and electro-deposition of N-phenylglycine onto the surface of highly conductive, few-layered, exfoliated flexible graphite sheets (EFGSs). At first, the promising features of the conjugative structure of the as-prepared protonated PNPG were thoroughly investigated by UV-vis absorption spectrophotometry, micro-Raman spectroscopy, and X-ray photoelectron spectroscopy analysis. The protonated nitrogen groups facilitate the rapid accessibility of counter ions from the electrolyte. Electrochemical studies revealed that the PNPG/E-FGS electrode exhibits an extraordinary areal specific capacitance of 367 mF cm(-2) at 10 mV s(-1). A flexible solid-state symmetrical supercapacitor was further fabricated using PNPG/E-FGS electrodes, exhibiting a specific capacitance as high as 199 mF cm(-2) at 1 mA cm(-2) with an operating voltage of 1.1 V. Furthermore, the device delivered an excellent specific energy of 8.36 mu W h cm(-2) at a power density of 1.65 mW cm(-2) in a working potential window of 1.1 V. More significantly, the energy density was nearly doubled to 16.1 mu W h cm(-2) upon extending the potential window from 1.1 to 1.5 V. The extremely redox-active CP electrode is highly suitable for applications in high-energy electrochemical capacitors with wide operating potential window.
Keywords: conducting polymer; electro-polymerization; exfoliated graphite; flexible supercapacitor; poly(N-phenylglycine)